MONITORING DRUG THERAPY IN X’s PHARMACY IN BADUNG REGENCY - Yanti Luh, Pratiwi Diva; Wirasuta, I M.A.G.; Asvinigita, Luh Rai Maduretno (Journal Pharmaceutical Science and Application; Vol 3 No 1 (2021): Journal Pharmaceutical Science and Application, 2021)
Background: Monitoring drug therapy based on Permenkes RI No. 73 of 2016 is one of the pharmaceutical care standards in pharmacy practice. Monitoring drug therapy is a process that includes activities to ensure safe, effective and rational drug therapy for patients. Patients who receive drug therapy are at risk of experiencing drug-related problems. Objective: This study aims to determine the implementation of monitoring drug therapy in one pharmacy in Badung Regency. Methods: The type of research is a descriptive observational study conducted by interview session one pharmacist in X Pharmacy, then analyzed descriptively according to Permenkes RI No 73 of 2016. Results: The results showed that in January-June 2020 there were 34 patients with disease categories requiring monitoring drug therapy: 27 patients with asthma (79%), six patients with diabetes (18%), and one patient with tuberculosis (3%). Patients with the largest visits were geriatric, which were 19 out of 34 patients. Conclusion : The monitoring of drug therapy at Pharmacy X has fulfilled all the parameters in the Standard Operating Procedure (SOP) for the implementation of in Pharmacy based on Permenkes RI No.73 of 2016. Keywords : Monitoring drug therapy, Implementation, Pharmacy, Pharmacist